2021
DOI: 10.3389/fmicb.2021.691563
|View full text |Cite
|
Sign up to set email alerts
|

Leptothrix cholodnii Response to Nutrient Limitation

Abstract: Microorganisms are widely utilized for the treatment of wastewater in activated sludge systems. However, the uncontrolled growth of filamentous bacteria leads to bulking and adversely affects wastewater treatment efficiency. To clarify the nutrient requirements for filament formation, we track the growth of a filamentous bacterium, Leptothrix cholodnii SP-6 in different nutrient-limited conditions using a high aspect-ratio microfluidic chamber to follow cell-chain elongation and sheath formation. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In the areas of life sciences and biomedical engineering, the flexibility to design and control a local environment has been utilized to create increasingly sophisticated organ-on-a-chip devices (Bhatia and Ingber, 2014), which are enabling the study of organogenesis in controlled environments. A similar approach (Kunoh et al, 2020(Kunoh et al, , 2021 is being adopted in microbiology with soil-on-a-chip devices (Stanley et al, 2016) that attempt to mimic the environment or manage interkingdom interactions in a controlled manner, which will aid in the study of microbial ecology. We anticipate that the techniques and infrastructure needed to fabricate and operate microfluidic devices will become (Fukuda et al, 2021) more widely available, increasingly important, and make fundamental contributions to microbial ecology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the areas of life sciences and biomedical engineering, the flexibility to design and control a local environment has been utilized to create increasingly sophisticated organ-on-a-chip devices (Bhatia and Ingber, 2014), which are enabling the study of organogenesis in controlled environments. A similar approach (Kunoh et al, 2020(Kunoh et al, , 2021 is being adopted in microbiology with soil-on-a-chip devices (Stanley et al, 2016) that attempt to mimic the environment or manage interkingdom interactions in a controlled manner, which will aid in the study of microbial ecology. We anticipate that the techniques and infrastructure needed to fabricate and operate microfluidic devices will become (Fukuda et al, 2021) more widely available, increasingly important, and make fundamental contributions to microbial ecology.…”
Section: Discussionmentioning
confidence: 99%
“…After clarifying single-filament dynamics, we investigated methods to control and modify the sheath, which may lead to practical methods for the management of bulking. We used microfluidics to exchange growth media quickly and easily in microfluidic devices, thereby permitting measurements of the effects of the abrupt limitation of different micronutrients on filament behavior (Kunoh et al, 2021). The findings obtained revealed that filament development under nutrient-deficient conditions may be classified into four general modes: (i) "normal", where the cell chain elongates without the appearance of intercellular gaps; (ii) "patchy", where large intercellular gaps appear within cell chains; (iii) "non-viable", where cell autolysis occurs before cell division may proceed; and (iv) "fragmented", where cell chains split into smaller chains (Fig.…”
Section: Section 3: 2d Confinement Reveals Dynamics Of Filament Forma...mentioning
confidence: 99%
“…Note that the subspecies affiliation of S. natans JCM 20382 is not determined (Gridneva et al 2011 ). Although these strains are not the type strains, they are commonly used as references to compare their phenotypic properties with those of related isolates (Sawayama et al 2011 ; Nott et al 2020 ; Kashiwabara et al 2021 ; Kunoh et al 2021 ). Growth under aerobic conditions was examined on GPPY agar (GPPY medium solidified with 1.5% agar) and APP medium at 25 °C for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…We considered the conjugation between WT* and S17-1 to be efficient when the cell surfaces of WT* cells were free from sheaths ( Figure 7 ). Since we previously reported that SP-6 cells become sheath-less when cultured in calcium-free conditions ( Kunoh et al, 2021 ), WT* cells cultured in routine MSVP were harvested and further cultured in MSVP lacking Ca (MSVP-Ca) for an additional 6 h (step M3) ( Figure 8A ). As expected, Figure 8B indicates that the conjugation efficiency with additional culturing in MSVP-Ca is approximately 2-fold higher than that without additional culturing (MSVP+Ca).…”
Section: Notesmentioning
confidence: 99%
“…We previously reported that sheath structure plays a critical role in holding aligned cell chains of SP-6 ( Kunoh et al, 2020 ), and that calcium depletion frequently results in breakage of cell filaments of SP-6 due to failure in the production of sheath structures encasing the cell chains ( Kunoh et al, 2021 ). From these findings, we hypothesized that preculturing SP-6 cells in a calcium-lacking medium might enhance the accessibility of E. coli cells to SP-6 cells for conjugation, which results in efficient gene transfer and subsequent gene replacement of SP-6 cells.…”
Section: Introductionmentioning
confidence: 99%